PERIZINAN BERUSAHA SEKTOR LINGKUNGAN HIDUP BERBASIS RISIKO SEBAGAI UPAYA MENJAGA KELESTARIAN LINGKUNGAN HIDUP - Matthew Delvian Suyana; Fieldo Nurviyan Ferdinand; Renard Kananda Dipta (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Indonesia, environmental problems are still a major problem. Related countries are also certainly urged by other countries or international institutions to carry out a settlement of these problems. This is because apart from having an impact on the country itself, environmental problems that occur in one country also have an impact on other countries either directly or indirectly. Conventionally, permits are an important instrument in the context of regulating and controlling activities or businesses to be carried out in a place. Licensing in this case is a very important legal instrument in relation to a control function. Enforcement and implementation of environmental law in Indonesia cover the areas of management and enforcement. In this case enforcement can be carried out through supervision and the application of government sanctions which are a step to enforce compliance or are repressive.